2017
DOI: 10.1080/10872981.2017.1352434
|View full text |Cite
|
Sign up to set email alerts
|

Do medical residents perform patient-centered medical home tasks? A mixed-methods study

Abstract: Background: Increasingly, residents are being trained in Patient-centered Medical Home (PCMH) settings. A set of PCMH entrustable professional activities (EPAs) for residents has been defined but not evaluated in practice. Objective: To understand whether residents trained at PCMH sites reported higher likelihood of engaging in PCMH tasks than those training in non-PCMH sites. Design: Survey and nominal group data from post-graduate trainees at three residency programs. Results: A total of 179 residents respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Residents who work with medical assistants and nurses throughout their tenure develop collaborative professional relationships, cultivating the skills needed to practice within a high-functioning team. 33,34 meaningfully to patient care and function at the highest level of their license. Also, patients interact consistently with at least one familiar member of a trusted team.…”
Section: Theme 1: Institutional Commitmentmentioning
confidence: 99%
“…Residents who work with medical assistants and nurses throughout their tenure develop collaborative professional relationships, cultivating the skills needed to practice within a high-functioning team. 33,34 meaningfully to patient care and function at the highest level of their license. Also, patients interact consistently with at least one familiar member of a trusted team.…”
Section: Theme 1: Institutional Commitmentmentioning
confidence: 99%
“…It has been demonstrated that residents trained at PCMH-recognized sites perform more PCMH-type skills. 11 The creation of a block rotation in a PCMH environment increases residents’ skills and knowledge about the model, but alone does not make them experts on PCMH. 12,13 How increased exposure to the PCMH model relates to a residency program’s ability to evaluate competency at these skills or evaluate milestones that relate to these skills has not been studied.…”
Section: Introductionmentioning
confidence: 99%